2019
DOI: 10.1039/c9nj02924a
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry, chemical biology and photophysics of certain new chromene–triazole–coumarin triads as fluorescent inhibitors of CDK2 and CDK4 induced cancers

Abstract: The chromene–triazole–coumarin triads synthesized through the MCR-Click strategy possess intense solution state fluorescence, intense solid-state fluorescence and CDK2/CDK4 targeted cytotoxic activity against human cervical cancer cells (HeLa).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In addition to two carbon atoms with sp 2 hybridization on the triazole ring, it is thought that three nitrogen atoms can make the system electron rich. Thus, it can be stated that electron transfer through triazole and coumarin rings is enabled and increases the absorption capacity of coumarin . This situation can be clearly seen in Table and Figures and .…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…In addition to two carbon atoms with sp 2 hybridization on the triazole ring, it is thought that three nitrogen atoms can make the system electron rich. Thus, it can be stated that electron transfer through triazole and coumarin rings is enabled and increases the absorption capacity of coumarin . This situation can be clearly seen in Table and Figures and .…”
Section: Resultsmentioning
confidence: 82%
“…Thus, it can be stated that electron transfer through triazole and coumarin rings is enabled and increases the absorption capacity of coumarin. [41] This situation can be clearly seen in Table 3 and Figures 7 and 8. Table 3 demonstrates that the molar absorption coefficient of the coumarin backbone before binding to triazole is lower.…”
Section: Triazole Effect On Absorption and Fluorescence Spectra Of Ctdmentioning
confidence: 82%
“…Moreover, being widely used in drug discovery [ 15 , 16 ], CuAAC has been applied in other areas, including bioimaging [ 17 , 18 ], biological [ 19 ], and biomedical [ 20 ] applications, synthesis of polymers [ 21 , 22 ] and dendrimers [ 23 , 24 ], and preparation of chemosensors [ 25 ], among others.…”
Section: Introductionmentioning
confidence: 99%
“…This supported them to be encapsulated into the hydrophobic pockets of CDK2 and CDK4. Furthermore, there is also a possibility of hydrogen bonding and π–cation interactions between the inhibitor molecules and CDK4 enhancing the binding affinities [ 37 ]. A recent study showed that the newly synthesized 4-flourophenylacetamide-acetyl coumarin (4-FPAC) IV produced cytotoxic effect and arrested metastasis in A549 as well as cell cycle progression at the G0/G1 by modulating p21, CDK2, and CDK4 expression [ 38 ] ( Figure 2 ).…”
Section: Introductionmentioning
confidence: 99%